Cara Kerja Statistik dalam Mengolah Data Pendidikan - Lenni Masnidar Nasution (Hikmah, 2015)
Statistics is the science that is very helpful for researchers to manage the data obtained can then become a starting point inference from the results of a study. Therefore, it is clear that the statistics have a pretty big role in the development of education in Indonesia. The development of statistical data processing has been growing rapidly, though as early researchers would have to understand first the terms or language used in the statistical analysis of the process of research, especially in educational research. This paper was written with the hope of repertoire of knowledge and additional readings for prospective researchers to be able to understand the prefix or introductory statistics. The main discussion in this paper is about statistics and statistics, data and data processing, as well as the frequency distribution.